Revisión de técnicas de evaluación formativa para el fortalecimiento de habilidades escritas, orales y prácticas en educación - Jara Ramírez, Milton Andrés; Palacios Vanegas, Hector Fabian; Jara Ramírez, Milton Andrés; Palacios Vanegas, Hector Fabian; Jara Ramírez, Milton Andrés; Palacios Vanegas, Hector Fabian (Corporación Universitaria Americana, 2025)
Introduction: this study analyzes the formative assessment techniques and mechanisms present in the academic literature, focusing on the development of written, oral and practical competencies, as well as on the subcategories related to learning objectives.  objective: to identify and categorize the formative assessment techniques and mechanisms used in the development of academic competencies, complementing the analysis with a bibliometric approach using the bibliometrix and biblioshiny packages in R-Studio; methodology: a search was carried out in the Scopus and WoS databases. Initially, 105 articles were considered, of which 28 were selected after applying the inclusion criteria established by PRISMA; results: there is evidence of a scarcity of studies in Spanish compared to international studies. The implementation of formative assessment techniques has gained relevance since the pandemic, highlighting written assessments that foster skills such as clear communication, text analysis, the correct application of grammatical and spelling rules, as well as the improvement of argumentation and the adaptation of writing to different contexts; conclusions: the active participation of students in formative assessment favors their integral development, improves their academic performance and promotes a proactive approach to continuous learning.